(untitled) (Bioagro, 2020)
The search for organic alternatives that replace chemical fertilization is a worldwide trend, given the need to obtain agricultural products with lower environmental costs, a line in which this research is framed. The effect of foliar applications of vermicompost leachates of bovine and goat manure on growth, chlorophyll content and yield of pepper (Capsicum annuum L.) hybrid Salvador under semi-protected conditions was evaluated. The study was carried out in the Experimental Field of the Universidad Técnica de Manabí, located in the Santa Ana canton, Manabí, Ecuador, in 2016. The experiment was conducted in a randomized complete block design with four replications and seven treatments, consisting of 1:10, 1:20 and 1:30 (v/v) dilutions of vermicompost leachate of bovine and goat manure, plus a control without bioproducts. The height of the plants, amount of leaves, chlorophyll index and yield increased significantly with the application of the vermicompost leachate from bovine and goat manure. The highest yield was achieved with the 1:30 (v/v) treatment of leachate from the vermicompost of goat manure, which increased the yield by approximately 4.71 Mg∙ha-1. The effectiveness of vermicompost as organic fertilizer was proven.